Optimization and Wear Properties for the Composites of Metal Matrix AA8011/Boron Nitride Using Taguchi Method. (8th February 2022) - Kumar, B. S. Praveen; Shobha, K. R.; Singh, Manoj Kumar; Rinawa, Moti Lal; Madhavarao, S.; Wadhawa, Gurumeet C.; Alrebdi, Tahani A.; Christopher, David
Abstract : In automotive and aircraft design, a new emerging material known as AA8011 metal matrix composite has earned a place for the reason that it is extremely durable and extremely hard. Newer composite variants were created and selected because of the demand for improved tribological performance. This study's objective is to find out how an AA8011-Boron Nitride metal matrix composite (MMC) wears out under different loads and sliding speeds. AMMC fortified with Boron Nitride particles are created using the powder metallurgy route and contain weight fractions ranging from 10% to 15% of the AA8011 and 37 μ m Boron Nitride particles. The material is made in an electric melting furnace through a stir casting procedure. Next, the materials are tested to see how long they will last in a tribotester set up like this: a block on a roller. With a controlled experimentation strategy, wear data can be collected using the L27 Taguchi method. Dry sliding wear of composites is controlled by four parameters: Boron Nitride substance, load-bearing capacity, slid speed, and sliding time. An analysis of variance is used to determine their effects. Sliding speed, friction, and normal load all have an effect on how much dry sliding wear occurs. In addition, the least amount of wear is obtained by combining the four controlling parameters optimally.